2019
DOI: 10.1097/md.0000000000017053
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment with Xiaoqinglong formula for bronchial asthma

Abstract: Background:Bronchial asthma is one of the most common chronic diseases in the world and has become a serious public health problem. Combination therapy has become the first choice for clinical treatment of bronchial asthma. In addition to the combined use of routine medication, traditional Chinese medicine as an adjuvant therapy is also considered. Xiaoqinglong Decoction (XQLD) is an effective prescription of traditional Chinese medicine in treating asthma, and there are more and more clinical reports about it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…In recent years, with the aggravation of environmental problems, its morbidity and mortality rates are gradually increasing, bringing a huge burden to public health security. 16 As previously reported, patients with asthma showed lower FEV1 and higher IgE levels during the acute episode. 17,18 In the current study, 70 asthma children and 66 healthy controls were recruited.…”
Section: Discussionsupporting
confidence: 54%
“…In recent years, with the aggravation of environmental problems, its morbidity and mortality rates are gradually increasing, bringing a huge burden to public health security. 16 As previously reported, patients with asthma showed lower FEV1 and higher IgE levels during the acute episode. 17,18 In the current study, 70 asthma children and 66 healthy controls were recruited.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, it is necessary to develop new and significant treatments for asthma. Clinical studies have found that traditional Chinese medicine (TCM), a type of alternative medicine, has good clinical effects on asthma [ 6 – 8 ]. As a supplementary medicine, TCM is widely used in the treatment of asthma with good results and few side effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…TCM has been widely used and demonstrated to be effective in the treatment of bronchial asthma (8)(9)(10). Zhike pingchuan granules (ZKPC) play a role in relieving coughing and reducing Zhike pingchuan granules improve bronchial asthma by regulating the IL-6/JAK2/STAT3 pathway YUMEI REN 1* , YULING LIU 2* , SHOUCHUAN WANG 3,4 , ZHEN LEI 5 , YONGBIN YAN 6 , XUTAO GUAN 7 , JIANGHONG HOU 8 , SHAN ZHU 9 , HAIJUN SHAN 9 , XINLEI TIAN 9 , QUAN WANG 10 , CAIHONG CAO 9 , YINGYING ZHANG 9 and YUNFENG MA 11 1 (11) demonstrated that Ginkgo lactone showed anti-inflammatory and anti-oxidant effects in a rat model of Aβ 1-40 induced Alzheimer's disease, improving nerve injury and cognitive function. Thorpe et al (12) indicated that the Gingko biloba extract EGb 761 could inhibit inflammation and thermal hyperalgesia for the treatment of inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%